Analyse des mutations socio-environnementales induites par l’exploitation minière à Bétaré-Oya, Est-Cameroun - Eric Voundi; Philippes Mbevo Fendoung; Patrick Essigue Emossi (VertigO)
East region of Cameroon concentrates the large share of proven and potential mineral resources of the country. It is currently the main focus of mining especially in the town of Bétaré-Oya. This activity has increased since 2007 with the "Operation Safeguard gold" launched by the ministry of Mines in preparation of the impoundment hydroelectric dam at Lom Pangar. However, the environmental changes that the mining activities induce question the long-term development prospects of the localities and raise many problems. This study is based on an empirical approach. It analyzes the environmental changes induced by extractive activities in Bétaré-Oya in order to assess environmental justice issues. It emerges that these issues locally formulated the taking into account, beyond the material and financial compensations, the collective identity of impacted communities, their relations of attachment to the territory, their needs/concerns, their culture, their territorial rights and their right to a decent life consistent with their values ​​and beliefs. The participation of these communities in decision-making is then necessary to properly articulate the sustainability of environmental changes brought, preserving links between nature and cultural heritage, and support communities in their legitimate aspirations for prosperity